PARTISIPASI KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 1 WADASLINTANG - Fathah Nurjanah; Maryono Maryono (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2018)
This research was aimed; 1) to know the quality of islamic religious education at theSMK N 1 Wadaslintang, 2) to know the participation of school commitee in increasingthe quality of islamic religious education at the SMK N 1 Wadaslintang, 3) to know thesupport and handicap factors how did school commite in increasing the quality of islamicreligious at the SMK N 1 Wadaslintang. In this research, we used a qualitative research.Qualitative search is a research that aimed to understand a phenomenon about what’sfelt by research subject holisticly with the words or language. In the collecting data, weused the interview, participant observation and documentation study. And analizing data,we wear the interactive analisis that ie data collection, data reduction , data displayand verification. The result of research had showed taht 1) quality of islamic religiouseducation is so good, it showed by activity of dhuha worship and dhuhur done togetherlyand on Friday, they go to mosque to pray togetherly.2) role of the school commitee inincreasing quality of islamic religious education such as : as a advisory agency, asa supporting agency, as a controlling agency, and as a executive agency. 3) factor ofsupporting as below a good leadership, a good performance of teacher and participationof studentadults and handicap factor were such as less of infrastructure and businessof school commitee.